Impact of Parental Involvement, Classroom Climate, and Behavior Problems on Academic Achievement of Children Between Rural and Urban Areas of Bangladesh - Mondal, Nilima Bala; Gain, Nityananda; Sarker, Bipul Kumar; Saifuddin, Kazi (The Indonesian Institute of Science and Technology Research, 2025)
The purpose of this study was to examine the relationship between parental involvement, classroom climate, and behavioral problems and their collective impact on children’s academic achievement. The research explores how parental involvement, classroom climate, and behavioral issues impact academic achievement in rural and urban Bangladeshi school-going children. 200 Bangladeshi secondary school students in grades VI–VII (100 in rural and 100 in urban areas; 50:50 gender ratio) participated in this study. Data was gathered by researchers using standardized instruments, such as child behavior checklists, classroom climate scales, parental involvement scales, and Personal Information Form (PIF). With a model that was a robust fit (Adjusted R2 = 0.754, F = 203.79, p < 0.05), the study deployed multiple regression to examine factors associated with academic success and found significant impacts on Parental Involvement (positive), Behavior Problems (negative), and Classroom Climate (positive). It is noted that academic achievement is strongly impacted by socio-economic status, place of residence, and their interaction (p < 0.05). This emphasizes how crucial these factors of context are. The study's limitations include the potential influence of unmeasured variables like teacher quality and regional disparities, which could affect academic outcomes. Additionally, reliance on self-reported parental involvement and classroom climate data might introduce biases, and the urban-rural comparison may oversimplify diverse contextual differences within these areas. The findings will guide educational psychologists, policymakers, and institutions in developing targeted strategies for improving student outcomes across different regions.